Bioprospecting of seahorse traded as traditional medicine : its nutritional values, antioxidation and anti-microbial activities - Rossita Shapawi; How, Siew Eng (Universiti Malaysia Sabah, 2013)
Sea horses are not well bioprospected based on scientific data though they are traded around the world for use as traditional medicines and aquarium fishes. Asian countries, including Malaysia are heavily involved in this trade which resulted in approximately 20 million sea horses are collected from the wild annually (Vincent, 1996). Sea horses are thought to resolve an extremely wide range of health problems despite the lacking of scientific data on nutritional value and active ingredients of the product. The present study conducted to analyse the nutritional values, total polyphenol content (TPC), anti-oxidation and antimicrobial activities of seahorse product available in the local market to support the alleged health benefits. Moisture, crude lipid, crude protein and crude ash were determined using standard methods (AOAC 1990). The TPC was assessed by the Folin-Ciocalteu's method, while the anti-oxidative activities were determined by two different methods; scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals and ferric reducing ability plasma (FRAP) assays. The antimicrobial properties of Hippocampus barbouri extracts were evaluated using disc diffusion method. The crude protein, crude lipid, ash and moisture contents (% dry weight) ranged from 58 - 69%, 0.6 - 5.2%, 18.7 - 26.8% and 14.6 - 19.0%, respectively. The control sample (live sea horses) showed significantly higher (P<O.OS) protein than the dried product. Male sea horses tend to have low content of lipid but high in ash compared to the females. Factors such as freshness and size of the seahorses may influence the proximate composition. The TPC content extracts of H. barbouriranged from 2.99 to 5.00 mg GAEjg. The ability to reduce DPPH was strongest in ethanol extract and lowest in ethyl acetate extract. Contradictory, the antioxidant property of H. barbouri in ethanol extracts are much lower than in ethyl acetate and methanol extracts. The values of TPC, DPPH and FRAP assays showed the existence of a significant negative relationship between DPPH and FRAP assays (r = 0.909, p<O.Ol). Only male ethyl acetate extract of H. barbouri showed anti-microbial activity against both C aureus and S. aureus. These findings indicated that seahorse, H. barbour; is a potential source of natural anti-oxidant and possess some anti-microbial activites against the harmful bacteria strain. The results obtained from the present study are important in the effort to conserve the species and promote seahorse aquaculture.